2016
DOI: 10.1117/12.2225440
|View full text |Cite
|
Sign up to set email alerts
|

Helmet mounted display supporting helicopter missions during en route flight and landing

Abstract: Degraded visual environment is still a major problem for helicopter pilots especially during approach and landing. Particularly with regard to the landing phase, pilot's eyes must be directed outward in order to find visual cues as indicators for drift estimation. If lateral speed exceeds the limits it can damage the airframe or in extreme cases lead to a rollover. Since poor visibility can contribute to a loss of situation awareness and spatial disorientation, it is crucial to intuitively provide the pilot wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Even so, in all studies evidence has been found that the head-up pathway concept could be superior to previous, nonconformal head-up solutions. 17 One of the most recent implementations of a tunnel-inthe-sky has been tested on a fully head-tracked HMD 32 (see Fig. 6).…”
Section: Tunnel Displaysmentioning
confidence: 99%
“…Even so, in all studies evidence has been found that the head-up pathway concept could be superior to previous, nonconformal head-up solutions. 17 One of the most recent implementations of a tunnel-inthe-sky has been tested on a fully head-tracked HMD 32 (see Fig. 6).…”
Section: Tunnel Displaysmentioning
confidence: 99%